(untitled) (The Pakistan Development Review, 2008)
The Economics of Corruption is a collection of papers covering both the theoretical as well as the empirical perspectives on corruption. It deals with various aspects of corruption and provides a well-integrated framework for research in this growing and active area of inquiry. Besides the first chapter, “Corruption: An Overview”, written by Ajit Mishra, which is an excellent review of the existing literature in the field, the book consists of ten articles divided by three themes. “Corruption as phenomena [sic] is always associated with an agency structure” writes Ajit in the introductory chapter of the book (p. 5). Corruption arises when the principal and agent have conflicting objectives and the principal fails to design the comprehensive enforceable contract due to lack of information. It becomes complicated when the principal puts an incentive scheme in place so as to induce optimal action by the agent and hires another agent to implement this incentive scheme, referred to as Supervisor. Ajit classifies this Principal-Supervisor-Agent problem, broadly, into three different types of relationships according to the powers and responsibilities enjoyed by the Supervisor.